DEVELOPING STUDENTS COMMUNICATIVE SKILLS IN EDUCATIONAL PROGRAMMES AT NON-LINGUISTIC FACULTIES - Druzhinina, Rimma (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The article addresses some issues of developing students’ communicative skills in foreign language teaching at non-linguistic faculties. The conceptual framework of the study follows the mode of professional competence approach. The study focuses on utilizing the project technology potential in students communication training. The topicality of the study is confirmed by a notable lack of data on the project technology application beyond the scope of regular English classes at non-linguistic faculties. Thus the study offers some new insights into the effects of the extracurricular project technology application for developing students’ communicative skills. Hence the aim of the study is to propose theoretical justification and methodological development of utilizing the extracurricular project technology potential as a means of facilitating students communication training in foreign language teaching. Following the aim we have examined the essence and characteristics of students’ communicative activities in foreign language teaching within extracurricular project cases. We have identified students communicative interaction algorithms and stages. We have designed a program for students communication training within the extracurricular project activities and elaborated a model of students’ communicative interaction backed by a collection of vocabulary and speech patterns. We have verified the findings gained from the study in our experimental practical work. Research and experience data obtained make it possible to identify the significance of extracurricular project activities in foreign language teaching for students communication training at non-linguistic faculties.